Cultural Determinants of Corporate Governance: A Multi-Country Study - Arantes, Pedro Paulo Melo; Peixoto, Fernanda Maciel; Carvalho, Luciana; Malaquias, Fernanda Francielle de Oliveira (Internext, 2020)
Purpose: The purpose of this study was to investigate if the culture of countries influences earnings management practices. Earnings management (EM) was chosen as a Corporate Governance mechanism. Methodology: We selected the Earnings Management proxies from Leuz et al. (2003). We adopted Hosftede´s cultural dimensions: power distance, individualism, uncertainty avoidance and long term orientation. The sample comprised companies listed in 2016 in the stock markets of Brazil, Argentina, Mexico, Chile, Colombia, Peru, and the United States. This work involved regression analysis to associate the dimensions of culture with the practice of EM of the firms. Findings: The results showed a positive relationship between EM and power distance and between EM and uncertainty avoidance. On the other hand, the results showed a negative relationship between EM and individualism and between EM and long term orientation. Overall, our results suggest that culture influences firms’ earnings management. Originality/value: Finance literature has had difficulty in assessing which variables can affect the development of CG in companies and its peculiarities in each country. It is also difficult to find country-level variables that are common to all countries. This paper breaks new ground by developing culture indicators of the countries and aggregating legal and firm-level variables to these indicators to advance the understanding of CG in the firms and nations. Theoretical and methodological contributions: studying culture at a multi-country level is important to improve the understanding of common aspects and the countries’ particularities that may affect the relationship between corporate governance and performance around the world.